La Persona como Eje Fundamental del Paradigma Humanista - Ayala Calderón, Javier (Acta Universitaria, 2008)
For the development of a humanist education it is necessary to center the pedagogical paradigm on the individual person, and to consider this person as an integrated totality. In this paradigm, education is considered to be a creative experience, and significant existential lessons are extracted from the learner’s own experience using active learning methods. Likewise, flexible, multi and trans-disciplinary programs are indispensible. In addition, self-evaluation is a permanent process of refl ection that can be applied to all aspects of life, not only those in the classroom. Finally, the most important values that the model promotes are respect, tolerance, and freedom, all of which are basic to human coexistence.